((Ré)-imaginer la communauté Walser : - Mathieu Petite (Revue de Géographie Alpine)
This paper focuses on an INTERREG IIIB project which aims to conserve and promote the so-called Walser culture. This case study shows how diverse stakeholders are involved in a network that transcends national borders. First, this paper analyses the process of construction of common attributes by stakeholders who do not usually interact. These attributes justify their cooperation. Second, it deals with the different ways to conserve Walser heritage. Similarly, the role of such a network in social cohesion and economic development is underlined.